Characterization of Florida, U.S. landfills with elevated temperatures. (December 2020) - Reinhart, Debra; Joslyn, Ryan; Emrich, Christopher T.
Highlights: Data for 27 Florida landfill were evaluated to determine the frequency of elevated temperatures. The majority of elevated temperature landfills received MSW or coal ash alongside unburned waste. Elevated temperature readings occurred in many gas wells rather than in a few outlier wells. Elevated temperatures were not predictive of low CH4 quality below approximately 150 °F. Abstract: The occurrence of elevated temperatures within landfills is a challenging issue for landfill operators to detect and correct. Little is known regarding the causes of elevated temperatures (ETs) or the number of landfills currently operating under such conditions. Therefore, the goal of this research was to determine which landfills within Florida have been impacted by ETs, and to develop a more complete understanding of the factors that may lead to these landfills becoming elevated temperature landfills (ETLFs). Historical landfill gas wellhead data, waste deposition reports, and landfill site geometry were collected for 27 landfill cells through the Florida Department of Environmental Protection electronic document management system, OCULUS database and from landfill operators and owners. These data were evaluated to quantify the characteristics that result in landfills having 'elevated' temperatures. Gas data included landfill gas temperatures and methane, carbon dioxide, and balance gas content. Furthermore, landfill maps were created in ArcGIS to observe spatial distribution of ETs in landfills over time. Upon analysis of the landfill gas wellhead data, it was discovered that 74% of studied landfill cells had ET readings; regulatory limits specify a maximum allowable gas temperature of 55 °C (131 °F). It was discovered that 37% of landfill cells contained MSW ash; of these cells, 90% of them are considered ETLFs. ETLF cells are on-average double the site area and approximately 6 m deeper than the average non-ETLF cell. Furthermore, results suggest that heat propagation in most landfills is limited; however, heat propagation is possible if gas wells are turned off for an extended time period.